Effect of Binary Hybrid Nanofluid Flow Between Parallel Plates With Applied Activation Energy - Alluguvelli, Ramesh; Shekar, Balla Chandra; Ali, Khasim; Shekhar, Rayaprolu Chandra (Communications in Mathematics and Applications, 2024)
This article examines the activation energy between two parallel plates consisting of MoS\(_2\)-GO-EO hybrid nanofluid. The nanoparticles, molybdenum disulphide (MoS\(_2\)) and graphene oxide (GO), are added to the base fluid, engine oil (EO). The influence of activation energy is also measured in this model. The finite difference method (FDM) is used to integrate the equations of motion, heat, and mass balance. The effects of important parameters such as activation energy, chemical reaction, temperature difference, random motion, and thermophoresis are discussed. The Nusselt number and skin friction are compared with available work to validate the numerical procedure. An enhanced Sherwood number is observed in Buongiorno's nanofluid model, while an elevated Nusselt number is seen with the hybrid nanofluid. Activation energy increases the profiles of temperature and concentration.